2021
DOI: 10.1128/mbio.00547-21
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin Modulation of the Colorectal Cancer-Associated Microbe Fusobacterium nucleatum

Abstract: Aspirin is a chemopreventive agent for colorectal adenoma and cancer (CRC) that, like many drugs inclusive of chemotherapeutics, has been investigated for its effects on bacterial growth and virulence gene expression. Given the evolving recognition of the roles for bacteria in CRC, in this work, we investigate the effects of aspirin with a focus on one oncomicrobe—Fusobacterium nucleatum. We show that aspirin and its primary metabolite salicylic acid alter F. nucleatum strain Fn7-1 growth in culture and that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 85 publications
(126 reference statements)
0
27
0
Order By: Relevance
“… 47 Moreover, the F. nucleatum isolated from the inflammatory intestinal epithelium of patients with IBD is more invasive than the strain isolated from healthy people or healthy intestinal epithelium of patients with IBD. 48 50 In addition, Klebsiella pneumoniae from the oral cavity can enter the intestinal tract ectopically, causing an increase in Th1 cells in the intestinal mucosa, thereby inducing IBD. 51 , 52 Clinical studies have also found that more oral-derived microorganisms can be detected in the intestinal mucosa and feces of patients with IBD.…”
Section: Oral Microbes and Digestive System Diseasesmentioning
confidence: 99%
“… 47 Moreover, the F. nucleatum isolated from the inflammatory intestinal epithelium of patients with IBD is more invasive than the strain isolated from healthy people or healthy intestinal epithelium of patients with IBD. 48 50 In addition, Klebsiella pneumoniae from the oral cavity can enter the intestinal tract ectopically, causing an increase in Th1 cells in the intestinal mucosa, thereby inducing IBD. 51 , 52 Clinical studies have also found that more oral-derived microorganisms can be detected in the intestinal mucosa and feces of patients with IBD.…”
Section: Oral Microbes and Digestive System Diseasesmentioning
confidence: 99%
“…PTGS2 ( COX2 ) upregulation is associated with F. nucleatum abundance in colon tumors ( 24 ). Additionally, aspirin, a modulator of PTGS2 , has long been recognized for its chemopreventive effect in the setting of colorectal cancers ( 76 ) and was recently demonstrated to reduce the development of colonic adenomas after F. nucleatum inoculation in the Apc min /+ mouse model ( 77 ). In our data, PTGS2 is among the most strongly differentially expressed genes in HCAE cells but is not differentially expressed in HCE cells, suggesting that the upregulation of PTGS2 and aspirin inhibition may be particularly important in some host cell or tissue contexts.…”
Section: Discussionmentioning
confidence: 99%
“…PTGS2 (COX2) upregulation is associated with Fn abundance in colon tumors (Kostic et al, 2013). Additionally, aspirin, a modulator of PTGS2, has been recently demonstrated to reduce development of colonic adenomas after Fn inoculation in the Apc min/+ mouse model (Brennan et al, 2021). In our data, PTGS2 is among the most strongly differentially expressed genes in invaded HCAE cells, but is not differentially expressed in HCE cells, suggesting that upregulation of PTGS2 and aspirin inhibition may be particularly important for invasive Fn strains.…”
Section: Discussionmentioning
confidence: 99%